(untitled) (Research, Society and Development, 2020)
This research aims to discuss and analyze the importance of sustainability in family farming on a rural property. Thus, it is necessary to investigate the level of sustainability present in the agroecosystems located in the city of Fagundes, in Agreste da paraíba. For this purpose, the MESMIS method was used, which addresses a series of social, economic and environmental indicators to diagnose sustainability in ownership of family agricultural production systems. 73.70% of the ecosystem’s indicators are in ideal situations, thus showing management close to adequate sustainability. In order to improve the productivity and sustainability of agricultural practices, recommendations were proposed to correct the weaknesses found, the measures aimed at elaborating the socioeconomic conditions of the family group and the place, in order to increase productivity in the agro-ecosystem.